Fuel cell technology for automotive applications, Fuel cell principles - Gao, Fei (IEEE, 2015)
In this first course, the basic physics in the proton exchange membrane (PEM) fuel cells and their material/structural composition, such as Bipolar plates, gas diffusion layer, catalyst layer and proton exchange membrane (electrolyte), will be introduced and explained. In addition to the PEM fuel cell technology, a short review of other fuel cell technologies will also be given. Topics covered include: Introduction to fuel cells;PEM fuel cell operating principals; Bipolar plates and gas channels; Gas diffusion layers (electrodes); Catalyst sites (electrodes); Electrolyte ? Polymer membrane; Cooling channels; Other fuel cell technologies ? SOFC, DMFC, PAFC, AFC and MCFC.